2024
DOI: 10.1007/s12008-024-01768-4
|View full text |Cite
|
Sign up to set email alerts
|

Machining performance optimization of graphene carbon fiber hybrid composite using TOPSIS-Taguchi approach

M. Murali Mohan,
Din Bandhu,
P. Venkata Mahesh
et al.

Abstract: Optimization of process factors plays a significant role in process efficiency and effectiveness. In this context, an attempt has been made to access the optimized machining factors for polymer nanocomposites including Graphene oxide (GO)/Carbon fiber (CF). To do this, graphene concentration (wt%), feed rate (FR), and spindle speed (SS) have been chosen as governing factors and their performances have been characterized by delamination value (DV) and thrust force (TF). After defining the levels for these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Recently, Wei et al reported changes in molecular interactions in ILs with charged SiO 2 surfaces. It is reported that the computational and experimental techniques are complementary for determining the structure, design, and thermophysical properties of liquids and their mixtures. Some researchers employed density functional theory (DFT), molecular dynamics (MD), COSMO-R, and Flory’s statistical theory (FST) to estimate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wei et al reported changes in molecular interactions in ILs with charged SiO 2 surfaces. It is reported that the computational and experimental techniques are complementary for determining the structure, design, and thermophysical properties of liquids and their mixtures. Some researchers employed density functional theory (DFT), molecular dynamics (MD), COSMO-R, and Flory’s statistical theory (FST) to estimate these properties.…”
Section: Introductionmentioning
confidence: 99%